Laparoskopická hysterektomie provedená ultrazvukovou operacní technikou: prospektivní studie - Holub, Z; Vorácek, J; Kliment, J; Lukác, J (Ceska gynekologie, 1999)
OBJECTIVE: The use of the harmonic scalpel and Laparosonic Coagulating Shears (LCS) for laparoscopic hysterectomy (LH) was evaluated in thirty six women with other gynaecological conditions. DESIGN: Prospective clinical study. SETTING: Department Gynaecology and Obstetrics, Endoscopic Training Centre, Baby Friendly Hospital Kladno, Kladno, Czech Republic. METHODS: Clinical data and cases of hysterectomy performed via ultrasonic operative laparoscopy were summarized and assessed. The primary hemostatic treatment was harmonic scalpel and LCS. Patients were assessed to efficacy, safety, utility and applicability of laparosonic operative technique. RESULTS: From all laparoscopic procedure were 91.6% successfully completed. There were three cases which were finished electrosurgically. The mean order of total operating time was 86.03 min and the mean order of blood loss was 170 ml (range 50-400 ml). There were no major complications, only one case of postoperative bleeding from vaginal cuff. CONCLUSION: Clinical prospective study demonstrates that ultrasonic activated technology in laparoscopic hysterectomy is easy to use, cost effective, and affords the surgeon a greater margin of safety. The harmonic scalpel produces surgical incision with concomitant hemostasis. This is only a preliminary report, and further randomised study is needed.
Keywords: Humans; laparoskopie; lidé středního věku; Female; Aged; Hemostatic Techniques; dospělí; Hysterectomy, Vaginal; senioři; lidé; hysterektomie vaginální; Adult; hemostatické techniky; ženské pohlaví; Middle Aged; Laparoscopy; ultrazvuk; Ultrasonics; prospektivní studie; Prospective Studies